Workload Dynamics and Employee Adaptation Strategies in Coping with Burnout in Three-Star Hotels in Surabaya: A Qualitative Study - Zainul Arifin; Abdul Halik; Siti Mujanah (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2026)
This study addresses the limited attention given to workload dynamics and burnout adaptation strategies among employees of three-star hotels in Surabaya, particularly within a business-city context. The originality of this research lies in its focus on “organic adaptation strategies” that emerge naturally from employees’ social interactions rather than formal organizational systems. The objective of this study is to explore the dynamics of employee workload and identify the adaptation strategies used to mitigate burnout. A qualitative descriptive approach with a case study design was employed, using in-depth semi-structured interviews, participatory observation, and documentation. Informants were selected through purposive sampling from operational departments. The findings reveal that workload is fluctuative yet consistently high, driven by multitasking demands, limited human resources, and high service expectations. These conditions trigger burnout manifested in emotional exhaustion, depersonalization, and reduced personal accomplishment. Employees respond through individual coping (e.g., prioritization and withdrawal) and social coping (e.g., teamwork and humor), with social strategies proving more effective in sustaining resilience. The study implies that hotel management should integrate psychological well-being into operational policies and formalize informal adaptive practices to create a more sustainable and human-centered work environment.